2009
DOI: 10.1152/ajpheart.00002.2009
|View full text |Cite
|
Sign up to set email alerts
|

Fenofibrate inhibits aldosterone-induced apoptosis in adult rat ventricular myocytes via stress-activated kinase-dependent mechanisms

Abstract: Aldosterone induces extracellular signal-regulated kinase (ERK)-dependent cardiac remodeling. Fenofibrate improves cardiac remodeling in adult rat ventricular myocytes (ARVM) partly via inhibition of aldosterone-induced ERK1/2 phosphorylation and inhibition of matrix metalloproteinases. We sought to determine whether aldosterone caused apoptosis in cultured ARVM and whether fenofibrate ameliorated the apoptosis. Aldosterone (1 microM) induced apoptosis by increasing terminal deoxynucleotidyltransferase-mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 46 publications
2
23
0
1
Order By: Relevance
“…We observed in our study that fenofibrate significantly reduced the activation of p38 and of AMPK in AR animals. It tended to the same for Erk 1/2, too Fenofibrate has been shown to inhibit stress-activated kinases such as p38 or Jnk in cardiac hypertrophy models in vitro (De Silva et al 2009;Irukayama-Tomobe et al 2004). Similar observations were also made for p38 in the kidneys of hypertensive rats treated with fenofibrate (Hou et al 2010).…”
Section: Discussionmentioning
confidence: 95%
“…We observed in our study that fenofibrate significantly reduced the activation of p38 and of AMPK in AR animals. It tended to the same for Erk 1/2, too Fenofibrate has been shown to inhibit stress-activated kinases such as p38 or Jnk in cardiac hypertrophy models in vitro (De Silva et al 2009;Irukayama-Tomobe et al 2004). Similar observations were also made for p38 in the kidneys of hypertensive rats treated with fenofibrate (Hou et al 2010).…”
Section: Discussionmentioning
confidence: 95%
“…The cardioprotective effects of SB203580 were shown to be closely associated with its ability to inhibit p38 MAPK. However, another study showed that SB203580 had minimal effects on aldosterone-mediated apoptosis (18). Of the several possible mechanisms which may underly the effects of aldosterone on cardiomyocyte apoptosis, our results suggest a key role for p38 MAPK activation that is known to be associated with cardiomyocyte apoptosis.…”
Section: Discussionmentioning
confidence: 55%
“…Pharmacological inhibitors of p38 MAPK have been shown to decrease myocyte apoptosis and improve cardiac function and heart failure in vitro and in vivo (16,17). However, a number of studies have demonstrated that SB203580, a p38 MAPK inhibitor, has minimal effects on aldosterone-induced apoptosis (18). Thus, whether the inhibition of p38 MAPK improves aldosterone-mediated apoptosis requires clarification.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in a setting of I/R, PPARa activation by its agonist WY-14643 has been implicated in the inhibition of apoptosis through modulation of Bcl-2 family proteins, specifically attributed to the upregulation of Bcl-2 and the concomitant downregulation of Bax [64]. In addition, in vitro studies demonstrated that fenofibrate inhibits JNK MAPK-dependent mitochondrial death pathway in aldosterone-induced apoptosis of adult cardiac myocytes [126].…”
Section: Ppars In the Regulation Of Cardiac Cell Deathmentioning
confidence: 99%